The time-dependent mechanical properties of fibre reinforced polymers - Dootson, M. (College of Aeronautics, 1968)
1. General Progress In the six months from April to September 1968 the task of primary importance has been to design lateral extensometers and to improve the longitudinal extensometer and consequently enable reproducable measurements of the deformations undergone by creep specimens to be made … [cont.].